If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(x + 5) + -40 = 0 Reorder the terms: (2 + x)(x + 5) + -40 = 0 Reorder the terms: (2 + x)(5 + x) + -40 = 0 Multiply (2 + x) * (5 + x) (2(5 + x) + x(5 + x)) + -40 = 0 ((5 * 2 + x * 2) + x(5 + x)) + -40 = 0 ((10 + 2x) + x(5 + x)) + -40 = 0 (10 + 2x + (5 * x + x * x)) + -40 = 0 (10 + 2x + (5x + x2)) + -40 = 0 Combine like terms: 2x + 5x = 7x (10 + 7x + x2) + -40 = 0 Reorder the terms: 10 + -40 + 7x + x2 = 0 Combine like terms: 10 + -40 = -30 -30 + 7x + x2 = 0 Solving -30 + 7x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (-10 + -1x)(3 + -1x) = 0Subproblem 1
Set the factor '(-10 + -1x)' equal to zero and attempt to solve: Simplifying -10 + -1x = 0 Solving -10 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -1x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = 0 + 10 -1x = 0 + 10 Combine like terms: 0 + 10 = 10 -1x = 10 Divide each side by '-1'. x = -10 Simplifying x = -10Subproblem 2
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Solution
x = {-10, 3}
| -12r=12 | | 4x^2-70x+6=0 | | 3x^2+8=38 | | 20u^3+65u^2-60u= | | 3x-5y=-33 | | 185=x-(.06*x) | | 9x^2-11=70 | | 185=x-(.06x) | | 2x^2+3y^2=35 | | 7y-5=5y+3 | | 3x^2-5y^2=-33 | | 3x^2+20x=3 | | 7-y=22 | | X+10-3x=16 | | 18y^3+3y^2-6y=0 | | 5(5+3x)=4x-8 | | 4(3c-1)-6=9c+2 | | 2t-2=3(t+2) | | 31-11=5(x-7) | | x+20+4x=-42-4x-46 | | -100=12x-4 | | 6+10x=256 | | 2x-7=3x+8 | | -4x-9=19 | | 700x-0.72=200x+0.58 | | X^2-14x+9=-11 | | 8x+4=5x+10 | | 8.1=10x+7.2 | | x-24=-7 | | -x=5(-6+7x) | | y-1.3=4 | | 11x+60=16 |